Coaching young athletes: the IOC Youth Athlete Development Model - Côté, J. (FINA Golden Coaches Clinic 2016, 2016)
Prof. Jean Côté Ph.D, Director, Queen`s University (School of Kinesiology and Health Studies) talks about "Coaching young athletes: the IOC Youth Athlete Development Model" at the FINA Golden Coaches Clinic 2016 (27:18 min).